Clinical and Health System Determinants of Venous Thromboembolism Event Rates After Hip Arthroplasty: An International Comparison. Issue 10 (October 2018) - Januel, Jean-Marie; Romano, Patrick S.; Couris, Chantal M.; Hider, Phil; Quan, Hude; Colin, Cyrille; Burnand, Bernard; Ghali, William A.
Abstract : Background: Routinely collected hospital data provide increasing opportunities to assess the performance of health care systems. Several factors may, however, influence performance measures and their interpretation between countries. Objective: We compared the occurrence of in-hospital venous thromboembolism (VTE) in patients undergoing hip replacement across 5 countries and explored factors that could explain differences across these countries. Methods: We performed cross-sectional studies independently in 5 countries: Canada; France; New Zealand; the state of California; and Switzerland. We first calculated the proportion of hospital inpatients with at least one deep vein thrombosis (DVT) or pulmonary embolism by using numerator codes from the corresponding Patient Safety Indicator. We then compared estimates from each country against a reference value (benchmark) that displayed the baseline risk of VTE in such patients. Finally, we explored length of stay, number of secondary diagnoses coded, and systematic use of ultrasound to detect DVT as potential factors that could explain between-country differences. Results: The rates of VTE were 0.16% in Canada, 1.41% in France, 0.84% in New Zealand, 0.66% in California, and 0.37% in Switzerland, while the benchmark was 0.58% (95% confidence interval, 0.35–0.81). Factors that could partially explain differences in VTE rates between countries were hospital length of stay, number of secondary diagnoses coded, and proportion of patients who received lower limb ultrasound to screen for DVT systematically before hospital discharge. An exploration of the French data showed that the systematic use of ultrasound may be associated with over detection of DVT but not pulmonary embolism. Conclusions: In-hospital VTE rates after arthroplasty vary widely across countries, and a combination of clinical, data-related, and health system factors explain some of the variations in VTE rates across countries. Abstract : Supplemental Digital Content is available in the text.